Pengaruh Integritas Pegawai, Etika Kerja, dan Loyalitas Pegawai terhadap Kinerja Pegawai di Cabang Dinas Pendidikan Menengah dan Pendidikan Khusus Kabupaten Kepulauan Aru - Rumra, Abudrahim Sofyan; Rahawarin, Mohammad Arsad; Zacharias, Tehubijuluw (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of employee integrity, work ethics, and loyalty on employee performance at the Branch Office of Secondary and Special Education in the Aru Islands Regency. A quantitative approach was employed, using survey methods through questionnaires distributed to 100 respondents. Data analysis was conducted using multiple linear regression, along with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that partially, employee integrity and work ethics have a positive and significant effect on performance, while loyalty does not have a significant effect. However, simultaneously, all three independent variables have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.911 indicates that 91.1% of the variation in employee performance is explained by integrity, work ethics, and loyalty. These findings highlight the importance of fostering values of integrity and ethical work culture in improving employee performance. Moreover, evaluating employee loyalty is crucial to ensure it is active and contributive to organizational goals. This study recommends strengthening human resources through value-based and character-based development.